Technical report: numerical solution of heat distribution in convective oven by using alternating direction implicit method / Nurhanani Saari, Khairunnisa' Khairul Anwar and Nur Khairunnisa Akhirruddin - Saari, Nurhanani; Khairul Anwar, Khairunnisa'; Akhirruddin, Nur Khairunnisa (2017)
The convection oven baking was investigated with experimentally and numerically as a heat transfer process. The heat mechanism was defined by Fourier's Law and used the two-dimensional of mathematical model. The alternating direction implicit finite difference technique was used for the numerical solution of representative the model. The numerical solution then compared with the experimental which consider heat transfer only with constant thermal physical properties. The nodes of the heat distribution of experimental and numerical are compared by using relative error.